2015
DOI: 10.2989/20702620.2015.1048420
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of nutrient levels and nutrient resorption inAvicennia marinaleaves in Yingluo Bay, China

Abstract: Avicennia marina is a typical mangrove species of subtropical coastlines of China. However, little is known about the retention of nutrients by this species in oligotrophic, coastal environments. In this study, seasonal changes in nitrogen (N) and phosphorus (P) concentrations, N:P ratio and total phenolic concentration in A. marina leaves during senescence were studied. Avicennia marina leaves had high N and P concentrations but the seasonal pattern of N concentration was different from that of P concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…All the same, NRP and PRP values were lowest in spring when A. corniculatum grew rapidly. This is in agreement with the findings by Wei et al [9], which suggested that lower N and P concentrations of senescent leaves in growing seasons in comparison to other seasons make it difficult to resorb additional nutrients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All the same, NRP and PRP values were lowest in spring when A. corniculatum grew rapidly. This is in agreement with the findings by Wei et al [9], which suggested that lower N and P concentrations of senescent leaves in growing seasons in comparison to other seasons make it difficult to resorb additional nutrients.…”
Section: Discussionsupporting
confidence: 93%
“…Nutrient resorption during leaf senescence serves to reduce the plant's dependence on current nutrient supply, and has been recognized as one of the most important strategies used by plants to conserve nutrients [8,9,34,35]. It has been estimated that approximately 50% of the nutrients (N and P) are resorbed during leaf senescence [29,36].…”
Section: Discussionmentioning
confidence: 99%
“…And up to 72% for P resorption by Alongi (2002), also P resorption has been reported for a number of Avicennia marina stands Ochieng and Erftemeijer, 2002;Alongi et al, 2005;Lovelock et al, 2007Lovelock et al, , 2010Lovelock et al, , 2011Zhou et al, 2010;Wei et al, 2015). Additionally, iron resorption in mangroves has not been assessed as yet.…”
Section: Introductionmentioning
confidence: 98%